John Carroll and Religious Liberty: Catholicism, Liberalism, and Church–State Rapprochement in Early America - Theodore Madrid (Religions, 2025)
This article aims to provide an account of the political thought of Archbishop John Carroll on the topic of religious liberty as a core principle of the American founding. It examines the relationship of Church and State through the lens of a developing self-understanding in the American and Roman Catholic identities. American Catholic colonists were accused of having a divided allegiance that made them dangerous to the social compact, divided between papal authority and the authority of the republic. Further, the place of the Catholic Church in a more pluralistic religious landscape following the Reformation demanded a reexamination of the traditional Catholic teaching on religious liberty. One man in particular stands out as a seminal figure in the development of a rapprochement between the American liberal understanding of religious liberty and that of the Catholic tradition. This man was Archbishop John Carroll, the first Roman Catholic Bishop in America. Carroll’s theoretical and practical approach to the highly contentious issue of religious liberty is a noteworthy example of simultaneous commitment to the Catholic faith and responsiveness to the exigencies of the moment and the perennial demands of political life. Carroll’s example is useful for Catholics and all others, as a model for Church–State separation.